ALLERGIC RHINITIS AND IMPORTANCE OF FEXOFENADINE HCL SUSTAINED RELEASE MICROSPHERE AS ITS TREATMENT APPROACH - AREFIN, PAROMA; HABIB, MD SHEHAN; AHMED, NAZIM UDDIN; RAHIM, MD ABDUR; IBRAHIM, MD; BHATTACHARJEE, SREEBASH CHANDRA; CHAKRABORTY, DIPANKAR; DAS, SUMON; KARMAKAR, DEBABRATA; BHOWMIK, DIP; et al. (International Journal of Applied Pharmaceutics, 2022)
The current treatment approaches for allergic rhinitis are practiced over decades, but the patient quality of life has not yet changed so much. The reasons are research gaps in pathophysiology of the disease, proper management of the disease. Fexofenadine HCl is a second-generation antihistamine drug which has a half-life of about 14.4 h. It is useful in the management of common symptoms like sneezing, itchy throat, and red eyes in individuals suffering from allergic rhinitis. Fexofenadine immediate release or sustained release formulations are available in the market as suspension, tablet and capsule. In this research paper, we have discussed the symptoms associated with allergic rhinitis and treatment approaches. Fexofenadine HCl is being used for the treatment of this disease. But as it has a long half-life, we have discussed the importance of the introduction of sustained-release microsphere formulation of Fexofenadine HCl in the market.